(untitled) (International Seven Journal of Multidisciplinary, 2025)
Objective: To compare the interstitial histopathological changes in the kidneys of dogs with chronic kidney disease (CKD) at different stages, evaluating the progression of fibrosis, inflammatory infiltration, and tubular atrophy, as well as their correlation with the clinical severity of the disease. CKD is one of the main causes of morbidity in dogs, characterized by a progressive and irreversible degeneration of the renal parenchyma. The development of interstitial fibrosis and the loss of the functional structure of the nephrons compromise renal capacity, leading to metabolic and hemodynamic dysfunctions. Histopathological analysis is essential to understand the evolution of the disease and direct more effective therapeutic approaches. In the early stages of CKD, mild to moderate interstitial inflammation and interstitial edema are observed, while in the advanced stages, extensive fibrosis and tubular atrophy predominate. The progression of renal fibrosis is associated with a worse prognosis, highlighting the importance of early diagnosis and appropriate clinical management.